DEVELOPMENT OF INNOVATIVE INFORMATION TECHNOLOGIES IN UZBEKISTAN - Anna Matyazova Vadimovna (American Journals Publishing, 2023)
During the years of independence, Uzbekistan made significant progress in introducing modern information technologies. The government has implemented a number of policies and initiatives aimed at stimulating the development of the technology sector, thus making Uzbekistan a regional center of innovation.